2016
DOI: 10.1007/s00204-016-1824-6
|View full text |Cite
|
Sign up to set email alerts
|

Information-dependent enrichment analysis reveals time-dependent transcriptional regulation of the estrogen pathway of toxicity

Abstract: The twenty-first century vision for toxicology involves a transition away from high-dose animal studies to in vitro and computational models (NRC in Toxicity testing in the 21st century: a vision and a strategy, The National Academies Press, Washington, DC, 2007). This transition requires mapping pathways of toxicity by understanding how in vitro systems respond to chemical perturbation. Uncovering transcription factors/signaling networks responsible for gene expression patterns is essential for defining pathw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…ZNF217 has previously been shown by our work ( Pendse et al, 2017 ) and others ( Frietze et al, 2014 ) to be a critical component of estrogen signaling and an important prognostic factor for breast cancer ( Vendrell et al, 2012 ). Similarly, TFAP2C is known to modulate ESR1 and GPR30 expression, and attenuate the expression of several estrogen-targeted genes ( Woodfield et al, 2007 ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…ZNF217 has previously been shown by our work ( Pendse et al, 2017 ) and others ( Frietze et al, 2014 ) to be a critical component of estrogen signaling and an important prognostic factor for breast cancer ( Vendrell et al, 2012 ). Similarly, TFAP2C is known to modulate ESR1 and GPR30 expression, and attenuate the expression of several estrogen-targeted genes ( Woodfield et al, 2007 ).…”
Section: Resultsmentioning
confidence: 62%
“…In our previous work for the Mapping the Human Toxome project ( Kleensang et al, 2014 ; Bouhifd et al, 2015 ), we demonstrated that using non-inferential statistical methods that did not depend on existing annotations such as IDEA ( Pendse et al, 2017 ) and WGCNA ( Maertens et al, 2015 ) offered a powerful method to untangle possible regulatory mechanisms and providing insight into possible Pathways of Toxicity compared to either inferential-based methods or approaches such as pathway enrichment analysis that depend exclusively on annotations. Building upon our previous work using WGCNA applied to in vitro transcriptomic data to more fully understand the transcription factors that are driving the biology of estradiol ( Pendse et al, 2017 ), we used WGCNA to examine a previously published transcriptomic dataset ( Shioda et al, 2013 ). Briefly, Shioda et al (2013) aimed to study the sensitivities of estrogen responsive genes to various endocrine disrupting chemicals (EDCs) based on the transcriptomic profile of MCF-7 cells exposed to either estrogen or several xenoestrogens (including BPA) over a dose-response curve ranging from picomolar to micromolar concentrations for a 48 h time period.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that coregulated gene clusters activated distinct groups of downstream biological processes, with the AHR-bound genomic cluster enriched for metabolic processes and the AHRunbound non-genomic cluster primarily activating immune processes. This work, together with the other recent studies of the peroxisome proliferator-activated receptor alpha (PPARα) and estrogen receptor pathways (McMullen et al 2014;Pendse et al 2016), illustrates the application of bioinformatic and statistical tools for reconstruction and analysis of the transcriptional regulatory cascades underlying cellular stress response. While these network reconstructions are species, tissue, and condition-specific, we anticipate that next-generation models that use machine learning to predict network structure and dynamics from genomic sequence and epigenomic features will soon be available.…”
Section: Conclusion and Discussionmentioning
confidence: 83%
“…The impact of individual nutrients, hormones and factors on the transcriptional expression of various markers in culture of breast cancer and/or mammary cells has been studied before, e.g., reports on the effect of estrogen on transcriptional activity in various cell lines [ 42 , 43 , 44 , 45 , 46 , 47 ], but none of these studies have explored the long-term effects of supplementation with complex set of hormones/growth factors on transcriptomic profile of phenotype defining genes in breast cancer cell lines for exposure longer than five days [ 45 ]. Therefore, this is the first characterization of the long-term effects of complex hormone/growth factor set on the expression of breast cancer/mammary markers in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%